Becoming Independent - Y. Chen; Y. Feng; Y. Wang; F. Fei. (Grounded Theory Review: An International Journal)
The popularisation of Glaser’s grounded theory (GT) methodology in China over the past two decades or so has seen some faithful use of classic (Glaserian) GT in several areas (i.e. psychology, culture of rule of law, and nursing) amid the overall misuse and abuse of the methodology. And arising from these endeavours are some life-changing experiences of GT researchers leading towards their academic independence. These individual experiences cover three intertwining aspects, namely inspiration and empowerment of Glaser and his methodology, developing a critical mind, and growth in personal character.